Implementation of Digital Marketing to Increase Sales at Pizza Gaza MSMEs - Husni Mubarok; Rambat Lupiyoadi (Eduvest - Journal of Universal Studies, 2026)
Pizza Gaza is a culinary MSME that produces and distributes frozen pizzas through a reseller network with social media engagement in the form of humanitarian contribution to Palestine. The main issues facing this enterprise are suboptimal digital marketing and declining sales performance during a specific period. This research aims to implement a digital marketing plan at Pizza Gaza to expand market reach, increase brand visibility, and encourage sales improvement. The research uses a qualitative approach with a business coaching method. Primary data is collected through in-depth interviews, observation, and documentation, then analyzed using the frameworks of Business Model Canvas (BMC), Value Proposition Canvas (VPC), PESTEL, VRIO, SWOT, and gap analysis. Based on the results of this analysis, a digital marketing plan is designed and implemented through brand positioning, content pillars, content calendars, marketing funnels, and paid social media advertising campaigns through Meta Ads and TikTok Ads. Research results show that implementing this plan successfully increased Pizza Gaza brand visibility and reached a wider audience. TikTok Ads demonstrated superior performance in reach and engagement, while Meta Ads proved more cost-efficient. There is evidence of improved sales post-campaign, marked by 13 new transactions and increased unit sales across various product variants. These findings demonstrate that targeted, data-driven digital marketing effectively supports MSME marketing performance.